Dyeing of Cotton Fabric using Pomegranate (Punica granatum) Aqueous Extract - ADEEL, SHAHID; ALI, SHAUKAT; A. BHATTI, IJAZ; ZSILA, FERENC (Asian Journal of Chemistry, 2010)
The decline in the use of artificial colourants due to their toxicity in food and textile industry, put forward by international market has increased the importance of natural raw materials. From those, pomegranate peel (Punica grantum) with solid applications is one of the most important sources of natural dyes. The major colouring component in pomegranate is tannins, extracted from the fresh and dried peels. The aim of present work is to evaluate pomegranate powder as natural textile dyestuff. The work consists of three steps, i.e. extraction, characterization and dyeing processes. The dye extraction procedure is conventional and traditional. Dyeing of different textiles, synthetic and natural fabrics with the extract of pomegranate powder has been carried out and dyeing has been optimized. Finally, dyed fabric have been subjected to different textile laboratory tests e.g., colour fastness, light fastness, washing fastness and rubbing fastness (dry and wet).